MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI MEDIA TEKA-TEKI SILANG BERGAMBAR BAGI ANAK TUNAGRAHITA RINGAN (Penelitian Tindakan Kelas di DV/C SLB Bina Nagari Solok Selatan) - Mirzandani - Mirzandani (Universitas Negeri Padang, 2012)
The background of this research begins with finding light mentally retarded students in class DV/C who get difficulties in reading for begining that is students who get difficulties in reading words that use letter (b, m, p) at the front, middle and last word. It is happened because the students often miss, change and add the letter while reading, low in mastering vocabulary, and also the use of media less optimally by the teacher. The purpose of this research is to know how the reading learning process run and want to know the increasing of ability of light mentally retarded students in class DV/C SLB Bina Nagari South Solok. This research is Classroom Action Research that is done in collaborative form with colleague. This research is done to two students as the subject of this research that is light mentally retarded students in class DV/C in SLB Bina Nagari South Solok. The result of this research along cycle I that was done in learning process of reading words that were consisted of letter (b, m, p) at the front, middle and alast word used cross word puzzle media woth pictures. Based on the average score that was got by the students at the end of cycle I, it can be shown that A got score 40% and 60% with help. Meanwhile, B got 30% and 70% with help. The result of students’ ability in cycle 2 in reading words that was done from the beginning of pointng the words, differentiating the words, mentioning the word, and filling in the boxes of cross word puzzle showed the increasing of their ability that was A got 60% without help and B got 50% without help. In cycle 2, learning process that was started by differentiating letter and filling in the cross word puzzle boxes showed teh increasing in students’ reading ability that was A got 80% without help and B got 70%. Based on the result of the research and the analysis data, it can be concluded that cross word puzzle media with pictures can increase the ability of reading words that use letter (b, m, p) at the front, middle and last word to light mentally retarded students in calas DV/C. Therefore, it is suggested to the head master, teacher, and the next researcher to use cross word puzzle media with pictures in increasing reading ability to light mentally retarded students.